Staging of Laryngeal Cancer: Clinicoradiological versus Histopathological Findings using Modified Laryngeal Sectioning - Shriyash Sinha; Sarmila Sen; Somnath Saha (Bengal Journal of Otolaryngology and Head Neck Surgery)
INTRODUCTION: Laryngeal cancer is commonly encountered in India. Post operative whole organ sectioning of the larynx, although informative, can often be tedious and cumbersome. This study aims to define a modified method of laryngeal sectioning and to assess its level of agreement with pre-operative clinicoradiological findings with regard to T-stage of laryngeal cancer.